Opportunities and barriers in the use of Toyota Kata: a bibliographic analysis - Michels, Everton; Forcellini, Fernando Antonio; Fumagali, Alissa Emanueli Cabrera (Revista Gestão da Produção Operações e Sistemas, 2019)
There is a gap in the literature regarding the opportunities and barriers in using Toyota Kata routines, which clarify some obscure aspects of Toyota. Thus, the objective of this article is to identify, through a theoretical, mixed, descriptive and bibliographical research, carried out through a systematic literature review, the opportunities and barriers found in the use of these routines. As these aspects are very specific, our results suggest that the main barriers encountered in various contexts are: 1 - lack of direction and environmental preparedness (awareness), 2 - lack of value stream map, and 3 - lack of meetings Coaching Kata In addition, the main opportunities were: 1 - short cycles, 2 - knowledge sharing, and 3 - adaptability. Thus, it can be concluded that these opportunities and barriers not only in manufacturing make Toyota Kata deployment less natural, but can be solved with simple actions, so future deployments do not go through the same problems as well, future works can empirically prove whether or not they are recurrent.